Equitable Use of ICT in Education: Issues and Concerns - Sharma, Sakshi; Alwani, Komal (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
ICT at present is impelling every aspect of human life. They are playing pivot roles in work places, business, education and entertainment. Moreover, many people recognize ICTs as facilitator for change, in working conditions, handling and exchanging information, teaching methods, learning approaches, scientific research and in accessing information communication technologies. In this digital era, the equitable use of ICT plays a pivotal role for providing teachers and students opportunities to learn and apply the latest techniques required in 21st century skills. Pre-service and in-service teachers as well as students need to know to a reasonable extent about the issues and concerns in the use of ICT for education. As teachers or potential teachers and students, they need to be above reproach. Teachers and students should understand the basic issues i.e. effectiveness, cost, equity and sustainability as well as the challenges i.e. infrastructure related challenges, capacity building challenges, challenges related to financing the cost of ICT use surroundings the use of ICT in education and then apply those issues as principle in practice. It was observed that equity has to do with the fact that quality education is provided to students through adequate provisions and equitable distribution of ICT facilities and resources to teachers and students, provisions of training services, equitable provision of electricity, internet and web services in schools in urban and rural areas through accessible roads. ICT improves teaching and learning and its importance for teachers in performing their role of creators of pedagogical environments. ICT makes a teacher efficient to present his teaching interestingly and able to learn the learners at any level of educational programmes. Today in India, teaching training programmes making useful and interesting by the term ICT. Infact, ICTs exemplified by the internet and interactive multimedia are obviously an important focus for future education and needs to be effectively integrated into formal teaching and learning especially in teacher education institutions.